Etika Guru Menurut Imam Ibnu Jama’ah As-Syafi’i Dalam Kitab Tadzkirotus Sami Wal Mutakallimi Fi Adabil Alim Wal Muta’alim - Ahmad Hadziq; Ahmad Zuhdi; Ngatoillah Linnaja (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The importance of good teacher ethics in the educational process is able to create a positive and productive educational environment that can affect academic learning, moral and social development for students. This research aims to: 1) find out the intraksi between teachers and students according to the book tadzkirotus sami' wal mutakallim fi adabil alim wal muta'alim; 2) knowing good teacher manners so that they are channeled and can set an example as a good example for students; 3) knowing the internal and external factors that can contribute to the teacher so that there is a misappropriation that affects the image of the teacher. This study uses a strong research approach where the type of research is library research. The results of this study show that: 1) good interaction between teachers and students in the book tadzkirotus sami' wal mutakallim fi adabil alim wal muta'alim, one of which is by sincerely intending to seek the pleasure of Allah SWT, patience, and gentleness. In addition, students are taught to always be polite to anyone, as well as interact positively which is emphasized to form relationships full of moral and ethical values. 2) Good teacher ethics can certainly create a positive and productive learning environment, including professionalism and providing a good example to form a good character in students. 3) Internal factors include a lack of ethical awareness and emotional pressure, then external factors, namely economic demands and lack of supervision that can result in the emergence of unethical behavior. To prevent these abuses, it is necessary to increase ethical leadership and increase supervision of character education for teachers and students.